Report on Development of Backward Hill Areas - Planning Commission (Planning Commission, 1981)
The Government of India Report on Development of Backward Hill Areas presents a comprehensive strategy for addressing the socio-economic and environmental challenges of India’s hilly regions, particularly in the Himalayan, Northeastern, and Deccan hill belts. Recognizing the unique geographical, climatic, and social conditions of these areas, the report advocates an integrated development approach centered on watershed-based planning, sustainable agriculture, livestock improvement, forest management, and infrastructure expansion. It emphasizes shifting from subsistence farming to cash crops, promoting hill-suitable industries, reducing out-migration through local employment generation, and improving basic amenities such as education, healthcare, electrification, and transport. The report also underscores community participation, environmental conservation, and targeted financial and administrative support as essential for sustainable development. Overall, it provides a holistic policy framework aimed at improving livelihoods while preserving the fragile ecology of India’s backward hill areas.
National Committee on the Development of Backward Areas
Planning Commission Government of India New Delhi March, 1981
Keywords: Backward Hill Areas; Integrated Hill Development; Planning Commission of India; Watershed Management; Agricultural Diversification; Horticulture Development; Livestock Improvement; Forest Resource Management; Rural Infrastructure; Employment Generation; Sustainable Development; Hill Area Policy